Our Extractive Age Expressions of Violence and Resistance - Shapiro, Judith; McNeish, John-Andrew (Routledge Studies of the Extractive Industries and Sustainable Development, 2021)
Our Extractive Age: Expressions of Violence and Resistance emphasizes how the spectrum of violence associated with natural resource extraction permeates contemporary collective life. Chronicling the increasing rates of brutal suppression of local environmental and labor activists in rural and urban sites of extraction, this volume also foregrounds related violence in areas we might not expect, such as infrastructural developments, protected areas for nature conservation, and even geoengineering in the name of carbon mitigation. Contributors argue that extractive violence is not an accident or side effect, but rather a core logic of the 21st Century planetary experience. Acknowledgement is made not only of the visible violence involved in the securitization of extractive enclaves, but also of the symbolic and structural violence that the governance, economics, and governmentality of extraction have produced. Extractive violence is shown not only to be a spectacular event, but an extended dynamic that can be silent, invisible, and gradual. The volume also recognizes that much of the new violence of extraction has become cloaked in the discourse of "green development," "green building," and efforts to mitigate the planetary environmental crisis through totalizing technologies. Ironically, green technologies and other contemporary efforts to tackle environmental ills often themselves depend on the continuance of social exploitation and the contaminating practices of non-renewable extraction. But as this volume shows, resistance is also as multi-scalar and heterogeneous as the violence it inspires. The book is essential reading for activists and for students and scholars of environmental politics, natural resource management, political ecology, sustainable development, and globalization.